2022
DOI: 10.1111/evj.13603
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of neutrophil gelatinase‐associated lipocalin are increased in serum and peritoneal fluid from horses with inflammatory abdominal disease and non‐strangulating intestinal infarctions

Abstract: Background Neutrophil gelatinase‐associated lipocalin (NGAL) is produced in response to inflammation in horses, but it has not yet been investigated as a biomarker in horses with the abdominal disease. Objectives To investigate NGAL in serum and peritoneal fluid in horses with the abdominal disease. Study design Retrospective clinical study. Methods Data from medical records of 270 horses admitted with acute abdominal disease (simple obstructions [n = 43], strangulating obstructions [n = 104], inflammatory abd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…Conversely, there was no significant difference in NGAL concentration between healthy horses and horses with simple or strangulating obstruction. 35 It was also found that NGAL concentration in serum was significantly higher in horses with a longer pre-admission duration of colic and was positively correlated with the concentration of SAA (r = 0.8) and fibrinogen (r = 0.5) and negatively correlated with serum iron (r = À0.5) and white blood cell count (r = À0.3). Based on these results, 35 NGAL would not be useful for differentiating horses with strangulating obstruction from horses that could be managed medically or from horses with enteritis from horses with a nonstrangulating intestinal infarction.…”
Section: Proteins and Other Inflammatory Markersmentioning
confidence: 88%
See 1 more Smart Citation
“…Conversely, there was no significant difference in NGAL concentration between healthy horses and horses with simple or strangulating obstruction. 35 It was also found that NGAL concentration in serum was significantly higher in horses with a longer pre-admission duration of colic and was positively correlated with the concentration of SAA (r = 0.8) and fibrinogen (r = 0.5) and negatively correlated with serum iron (r = À0.5) and white blood cell count (r = À0.3). Based on these results, 35 NGAL would not be useful for differentiating horses with strangulating obstruction from horses that could be managed medically or from horses with enteritis from horses with a nonstrangulating intestinal infarction.…”
Section: Proteins and Other Inflammatory Markersmentioning
confidence: 88%
“…In a study using banked serum and peritoneal samples from a large population of acute colic cases, NGAL was assessed specifically for its ability to differentiate between types of lesions causing colic 35 . Results showed that horses with nonstrangulating intestinal infarction caused by Strongylus vulgaris migration through the cranial mesenteric artery and inflammatory abdominal disease (enteritis, colitis, peritonitis) had significantly higher serum and peritoneal NGAL concentrations than the other horses with colic and healthy horses.…”
Section: Proteins and Other Inflammatory Markersmentioning
confidence: 99%
“…The aim of this retrospective clinical study by Malou Winther and co‐workers in Denmark was to investigate neutrophil gelatinase‐associated lipocalin (NGAL) in serum and peritoneal fluid in horses with abdominal disease .…”
Section: Neutrophil Gelatinase‐associated Lipocalinmentioning
confidence: 99%
“…Based on the origin of NGAL, several studies which discussed its ability to differentiate in ammatory and non-in ammatory disease in equine patients were published [20][21][22]. However, NGAL's diagnostic value of renal diseases in equine medicine has not yet been widely…”
Section: Introductionmentioning
confidence: 99%
“…Serum and plasma NGAL appeared to increase 24-72 h earlier than creatinine in humans and indicated the acute renal damage in several studies [13][14][15][16]. Urinary NGAL also showed promising results and was elevated as early as 2 h after ischemic renal damage [17][18][19].Based on the origin of NGAL, several studies which discussed its ability to differentiate in ammatory and non-in ammatory disease in equine patients were published [20][21][22]. However, NGAL's diagnostic value of renal diseases in equine medicine has not yet been widely…”
mentioning
confidence: 99%